Investigating the Effect of Anxiety, Uncertainty and Ethnocentrism on Willingness to Interact in an Intercultural Communication. (January 2015) - Logan, Shanna; Steel, Zachary; Hunt, Caroline
The current research aims to explore the effect of low or high perceived predictability and anxiety on willingness to interact with a person from another cultural group. How differences in anxiety, both individual (trait anxiety) and intergroup (anxiety specifically related to an interaction), influence willingness to engage within an intercultural communication is investigated. In addition, the contribution of ethnocentrism to willingness to interact is explored. Anxiety, uncertainty, and ethnocentrism are all important factors that negatively affect willingness to interact in an intercultural communication. Yet to date, anxiety and uncertainty have been examined separately to ethnocentrism in the literature. The current study found that an anxiety-provoking intercultural interaction has a negative impact on willingness to interact with an intercultural interaction partner. Perceived predictability alone was not found to affect willingness to interact, contrary to previous research, with results suggesting that intergroup anxiety may be a better predictor of willingness to interact than perceived predictability and trait anxiety. Overall results indicate that anxiety and uncertainty are separate but related constructs in support of current theoretical models. Ethnocentrism was shown to uniquely contribute to willingness to interact. This novel finding indicates the importance of cultural factors on willingness to engage in intercultural communication and points to the need for further research to explore the impact of cultural values on these relationships.